Tuff-based all-solid-waste cementitious material and preparation method thereof, and cementitious substance
Patent Information
- Application Number
- CN202611385808.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-16
AI Technical Summary
1)本发明以凝灰岩粉、高炉矿渣粉、钢渣粉及石膏类固废等工业固体废弃物为主要原料,构建全固废胶凝体系。其中,凝灰岩粉属于低活性火山灰类固废,在传统胶凝体系中高掺量使用时易导致体系反应受限及强度发展缓慢。本发明通过合理设计体系组成及引入高分子反应调控助剂,实现了凝灰岩粉在胶凝材料中的高掺量利用:以碱硫激发玻璃体固废体系为反应基底,在凝灰岩粉掺量不低于40%的条件下,引入特定结构的高分子反应调控助剂,通过其对钙、铝等反应离子的络合作用及对颗粒界面的吸附分散作用,调控硅铝相反应路径与反应速率,从而在不依赖强碱激发的条件下,提高体系反应效率和力学性能,显著提高了低活性固废资源化利用水平。
Smart Images

Figure CN122916531A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of industrial solid waste utilization, specifically to a tuff-based all-solid waste cementing material and its preparation method, as well as the cementing substance. Background Technology
[0002] Tuff powder, a typical volcanic ash-like solid waste, possesses high silica and aluminum content and potential cementing activity. However, due to its low glass phase content and stable mineral structure, its reactivity release is slow under weakly alkaline sulfur-activated conditions. Under high dosage conditions, tuff powder particles are prone to agglomeration, and the insufficient effective reaction interface in the system leads to limited dissolution of the silica and aluminum phase, low early reaction rates, and slow development of mechanical properties. Simultaneously, the tuff system is silica-rich and calcium-poor, making it susceptible to local ion concentration imbalances and early disordered precipitation during the reaction process, thus affecting the subsequent continuous growth and densification of the gel structure.
[0003] In existing technologies, the activation of low-activity solid waste materials mainly relies on increasing the alkalinity of the system or introducing strong alkaline activators to promote the dissolution of the silicon-aluminum phase. However, such methods usually have problems such as high alkali consumption, poor system stability, easy efflorescence, and limited engineering applications.
[0004] Therefore, how to achieve effective reaction control and performance improvement of high-content tuff powder systems without significantly increasing the alkalinity of the system remains a pressing technical problem to be solved in this field. (Summary of the Invention) This invention provides a tuff-based solid waste cementitious material and its preparation method, as well as the cementitious substance. Under conditions that do not rely on strong alkaline activators, this invention achieves the effective construction of a high-content tuff powder solid waste cementitious system and realizes effective reaction control and performance improvement.
[0005] This invention provides a tuff-based solid waste cementitious material, comprising the following components in parts by weight: 40-70 parts tuff powder, 20-50 parts blast furnace slag powder, 5-15 parts sulfate-containing solid waste powder, 5-16 parts alkaline solid waste powder, and 0.01-1 parts polymer reaction regulating agent. The functional groups of the polymer reaction regulating agent include one or more of carboxyl, amino, hydroxyl and sulfonic acid groups; The tuff-based solid waste cementitious material does not include strongly alkaline activators.
[0006] Preferably, the sulfate-containing solid waste powder includes one or more of desulfurized gypsum powder, fluorogypsum powder, and phosphogypsum powder.
[0007] Preferably, the alkaline solid waste powder includes one or more of steel slag powder, red mud powder, and calcium carbide slag powder.
[0008] Preferably, the polymer reaction regulating agent includes one or more of polyaspartic acid, polyethyleneimine, polyallylamine, polyvinyl alcohol, polyvinylpyrrolidone, sulfonated polystyrene, and carboxymethyl chitosan.
[0009] Preferably, the mass of the tuff powder is not less than 40% of the total mass of all components of the tuff-based solid waste cementitious material.
[0010] Preferably, the polymer reaction regulating agent is polyvinylpyrrolidone and carboxymethyl chitosan.
[0011] Preferably, the mass ratio of polyvinylpyrrolidone to carboxymethyl chitosan is 1:4.
[0012] Preferably, the following components are included in the following mass fractions: 50 parts tuff powder, 27.5 parts blast furnace slag powder, 10 parts desulfurized gypsum powder, 12 parts steel slag powder, 0.05 parts polyvinylpyrrolidone, and 0.2 parts carboxymethyl chitosan.
[0013] This invention also provides a method for preparing the tuff-based solid waste cementitious material described in the above technical solution, comprising the following steps: The components of the tuff-based solid waste cementitious material are mixed to obtain the tuff-based solid waste cementitious material.
[0014] The present invention also provides a cementitious material, characterized in that it comprises the following raw materials: water, the tuff-based solid waste cementitious material described in the above technical solution, or the tuff-based solid waste cementitious material prepared by the preparation method described in the above technical solution.
[0015] The present invention has the following beneficial effects: 1) This invention uses industrial solid wastes such as tuff powder, blast furnace slag powder, steel slag powder, and gypsum-based solid waste as main raw materials to construct a complete solid waste cementing system. Tuff powder, being a low-activity volcanic ash-type solid waste, is prone to limited reaction and slow strength development when used in high amounts in traditional cementing systems. This invention achieves high-volume utilization of tuff powder in cementing materials through rational system composition design and the introduction of polymeric reaction regulators: using an alkali-sulfur activated vitreous solid waste system as the reaction base, and with a tuff powder content of not less than 40%, a polymeric reaction regulator with a specific structure is introduced. Through its complexation effect on calcium, aluminum, and other reactive ions and its adsorption and dispersion effect on the particle interface, the reaction path and reaction rate of the silicon-aluminum phase are controlled. This improves the system's reaction efficiency and mechanical properties without relying on strong alkali activation, significantly enhancing the resource utilization level of low-activity solid waste.
[0016] 2) Existing low-activity tuff solid waste cementing systems typically rely on strong alkaline activators such as sodium hydroxide and water glass to promote the reaction of the silica-alumina phase. However, these systems generally suffer from high alkali consumption, high cost, easy efflorescence, and poor construction safety. This invention, without introducing additional strong alkaline activators, regulates the system's reaction process through a polymer reaction-regulating agent, achieving effective reaction and strength development in high-content tuff systems, while reducing alkali consumption and engineering application risks.
[0017] 3) The polymeric reaction regulating agent used in this invention can complex key reactive ions in the system and improve the dispersion state of tuff particles, thereby inhibiting the formation of early disordered precipitation, improving the effective reaction interface, and promoting uniform reaction in the system. Compared with traditional activation methods that increase alkalinity, this invention focuses more on regulating the reaction process, improving the overall structural stability of the system while maintaining good construction fluidity.
[0018] 4) The preparation process of this invention is simple; the gelling material can be obtained simply by mixing the raw materials, without the need for high-temperature calcination, complex chemical modification, or energy-intensive activation treatment. It has the advantages of simple process, low energy consumption, and easy engineering application. At the same time, this invention can realize the synergistic high-value utilization of various industrial solid wastes, and has good economic and environmental benefits.
[0019] In summary, this invention achieves the effective construction of a high-volume tuff powder-based solid waste cementing system through polymer reaction regulation, without relying on strongly alkaline activators. This system features high tuff powder utilization, low alkali consumption, simple process, and green, low-carbon characteristics, providing a new technical approach for the large-scale resource utilization of low-activity volcanic ash-type solid waste. Attached Figure Description
[0020] Figure 1 The graph shows the flexural strength of the cementitious materials after molding in Examples 1-5 and Comparative Examples 1-5. Figure 2 The chart shows the compressive strength of the cementitious materials after molding in Examples 1-5 and Comparative Examples 1-5. Figure 3 The XRD pattern of Example 2; Figure 4 The XRD pattern of tuff; Figure 5 XRD pattern of steel slag. Detailed Implementation
[0021] This invention provides a tuff-based solid waste cementitious material, comprising the following components in parts by weight: 40-70 parts tuff powder, 20-50 parts blast furnace slag powder, 5-15 parts sulfate-containing solid waste powder, 5-16 parts alkaline solid waste powder, and 0.01-1.5 parts polymer reaction regulating agent. The functional groups of the polymer reaction regulating agent include one or more of carboxyl, amino, hydroxyl and sulfonic acid groups; The tuff-based solid waste cementitious material does not include strongly alkaline activators.
[0022] By weight, the tuff-based solid waste cementitious material of the present invention comprises 40-70 parts of tuff powder, which in specific embodiments of the present invention can be 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, or 69 parts; preferably, the mass of the tuff powder is not less than 40% of the total mass of all components of the tuff-based solid waste cementitious material, which in specific embodiments of the present invention can be 45%, 50%, 55%, 60%, 65%, 70%, or 75%; preferably, the specific surface area of the tuff powder is 180-500 m². 2 / kg, which in a specific embodiment of the present invention can be 200m 2 / kg, 250m 2 / kg, 280m 2 / kg, 300m 2 / kg, 320m 2 / kg, 350m 2 / kg, 380m 2 / kg, 400m 2 / kg, 450m 2 / kg or 480m 2 / kg.
[0023] Based on the unit mass parts of the tuff powder, the components of the tuff-based all-solid waste cementitious material of the present invention include 20-50 parts of blast furnace slag powder. In specific embodiments of the present invention, this can be 21, 22, 23, 24, 25, 26, 27, 27.5, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, or 49 parts; the specific surface area of the blast furnace slag powder is preferably 180-500 m². 2 / kg, which in a specific embodiment of the present invention can be 200m 2 / kg, 250m 2 / kg, 280m 2 / kg, 300m 2 / kg, 320m 2 / kg, 350m 2 / kg, 380m 2 / kg, 400m 2 / kg, 450m 2 / kg or 480m 2 / kg.
[0024] Based on the unit mass parts of the tuff powder, the components of the tuff-based all-solid waste cementitious material of the present invention include 5-15 parts of sulfate-containing solid waste powder, which in specific embodiments of the present invention can be 6, 7, 8, 9, 10, 11, 12, 13, or 14 parts; the sulfate-containing solid waste powder preferably includes one or more of desulfurized gypsum powder, fluorogypsum powder, and phosphogypsum powder; the specific surface area of the sulfate-containing solid waste powder is preferably 180-500 m². 2 / kg, which in a specific embodiment of the present invention can be 200m 2 / kg, 250m 2 / kg, 280m 2 / kg, 300m 2 / kg, 320m 2 / kg, 350m 2 / kg, 380m 2 / kg, 400m 2 / kg, 450m 2 / kg or 480m 2 / kg.
[0025] Based on the unit mass parts of the tuff powder, the components of the tuff-based all-solid waste cementitious material of the present invention include 5-16 parts of alkaline solid waste powder, which in specific embodiments of the present invention can be 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15 parts; the alkaline solid waste powder preferably includes one or more of steel slag powder, red mud powder, and calcium carbide slag powder; the specific surface area of the alkaline solid waste powder is preferably 180-500 m². 2 / kg, which in a specific embodiment of the present invention can be 200m 2 / kg, 250m 2 / kg, 280m 2 / kg, 300m 2 / kg, 320m 2 / kg, 350m 2 / kg, 380m 2 / kg, 400m 2 / kg, 450m2 / kg or 480m 2 / kg.
[0026] Based on the unit mass parts of the tuff powder, the components of the tuff-based solid waste cementitious material of the present invention include 0.01 to 1.5 parts of a polymer reaction regulating agent. In specific embodiments of the present invention, this can be 0.1, 0.2, 0.25, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.3, or 1.4 parts. The functional groups of the polymer reaction regulating agent include one or more of carboxyl, amino, hydroxyl, and sulfonic acid groups. The polymer reaction regulating agent is preferably a water-soluble polymer compound. More preferably, the polymer reaction regulating agent includes one or more of polyaspartic acid, polyethyleneimine, polyallylamine, polyvinyl alcohol, polyvinylpyrrolidone, sulfonated polystyrene, and carboxymethyl chitosan. More preferably, the polymer reaction regulating agent is polyvinylpyrrolidone and carboxymethyl chitosan, and the mass ratio of polyvinylpyrrolidone to carboxymethyl chitosan is preferably 1:4. The carboxyl, amino, hydroxyl, or sulfonic acid groups in the polymer reaction regulating agent have a complexing effect on calcium and / or aluminum ions in the system, which can regulate the release rate of reaction ions, inhibit the formation of early disordered precipitation, and improve the effective reaction interface by adsorption and dispersion on the surface of tuff powder particles, thereby guiding the silicon-aluminum phase to react along a reaction path that is conducive to the development of mechanical properties.
[0027] This invention also provides a method for preparing the tuff-based solid waste cementitious material described in the above technical solution, comprising the following steps: The components of the tuff-based solid waste cementitious material are mixed to obtain the tuff-based solid waste cementitious material.
[0028] This invention employs a method that combines a polymer reaction regulator with an alkali-sulfur activated solid waste system. By using the polymer reaction regulator to complex calcium and / or aluminum ions, the release and migration of key reactive ions are controlled. Furthermore, through its adsorption and dispersion effect on the surface of tuff particles, the effective reaction interface of the system is improved, thereby inhibiting the formation of early disordered precipitation, promoting the continuous dissolution of the silica-alumina phase and the orderly growth of the gel structure, and realizing the efficient utilization of high-content tuff powder under weakly alkaline conditions.
[0029] Furthermore, without introducing additional strong alkaline activators, this invention significantly improves the early and late mechanical properties of high-dosage tuff powder systems while maintaining good construction fluidity. This cementitious material can fully utilize various solid wastes, achieving synergistic and high-value utilization of resources, reducing traditional cement usage and alkali consumption, and lowering environmental impact. The resulting material exhibits high strength, good durability, low drying shrinkage, and cracking tendency, realizing the efficient synergistic utilization of various industrial solid wastes, reducing the use of traditional cement and strong alkalis, and providing a green technological approach for the high-dosage resource utilization of low-activity solid waste.
[0030] The present invention also provides a cementing material comprising the following raw materials: water, the tuff-based solid waste cementing material described in the above technical solution, or the tuff-based solid waste cementing material prepared by the preparation method described in the above technical solution.
[0031] The following detailed description of the tuff-based solid waste cementitious material, its preparation method, and cementing substances provided by the present invention, with reference to specific embodiments, should not be construed as limiting the scope of protection of the present invention.
[0032] Table 1. Main components of tuff, mineral powder and steel slag used in the examples
[0033] Figure 4 This is the XRD pattern of tuff. Figure 5 XRD pattern of steel slag.
[0034] The desulfurized gypsum was purchased from Lingshou Runming Mineral Products Co., Ltd.; the fluorogypsum, phosphogypsum and carbide slag were purchased from Zhucheng Jiuqi Building Materials Co., Ltd. in Shandong Province; and the red mud powder was purchased from Yantai Anda Environmental Protection Technology Co., Ltd. in Shandong Province.
[0035] Example 1 Weigh out 50 parts by weight of tuff powder, 27.5 parts by weight of blast furnace slag powder, 10 parts by weight of desulfurized gypsum powder, 12.5 parts by weight of steel slag powder, 0.05 parts by weight of polyvinylpyrrolidone and 0.2 parts by weight of carboxymethyl chitosan, and mix them evenly to obtain a polymer-controlled tuff-based solid waste cementitious material, denoted as S1.
[0036] Example 2 Weigh out 40 parts by weight of tuff powder, 40 parts by weight of blast furnace slag powder, 12 parts by weight of fluorogypsum powder, 8 parts by weight of carbide slag powder, 0.05 parts by weight of polyaspartic acid and 0.2 parts by weight of carboxymethyl chitosan, and mix them evenly to obtain a polymer-controlled tuff-based solid waste cementitious material, denoted as S2.
[0037] Example 3 Weigh out 50 parts by weight of tuff powder, 27.5 parts by weight of blast furnace slag powder, 10 parts by weight of desulfurized gypsum powder, 12.5 parts by weight of steel slag powder, 0.05 parts by weight of polyvinyl alcohol and 0.05 parts by weight of sulfonated polystyrene, and mix them evenly to obtain a polymer-controlled tuff-based all-solid waste cementitious material, denoted as S3.
[0038] Example 4 Weigh out 65 parts by weight of tuff powder, 22 parts by weight of blast furnace slag powder, 8 parts by weight of fluorogypsum powder, 5 parts by weight of red mud powder, 0.02 parts by weight of polyvinylpyrrolidone and 0.08 parts by weight of carboxymethyl chitosan, and mix them evenly to obtain a polymer-controlled tuff-based solid waste cementitious material, denoted as S4.
[0039] Example 5 Weigh out 40 parts by weight of tuff powder, 40 parts by weight of blast furnace slag powder, 10 parts by weight of phosphogypsum powder, 10 parts by weight of steel slag powder, 0.05 parts by weight of polyaspartic acid and 0.05 parts by weight of carboxymethyl chitosan, and mix them evenly to obtain a polymer-controlled tuff-based solid waste cementitious material, denoted as S5.
[0040] Example 6 Weigh out 40 parts by weight of tuff powder, 40 parts by weight of blast furnace slag powder, 12 parts by weight of fluorogypsum powder, 8 parts by weight of carbide slag powder, 0.1 parts by weight of polyaspartic acid and 1 part by weight of carboxymethyl chitosan, and mix them evenly to obtain a polymer-controlled tuff-based solid waste cementitious material, denoted as S6.
[0041] Comparative Example 1 Weigh 40 parts by weight of tuff powder and 60 parts by weight of P.I42.5 cement, mix them evenly to obtain a cement-based cementitious material containing tuff powder, denoted as R1.
[0042] Comparative Example 2 Weigh out 40 parts by weight of tuff powder, 60 parts by weight of P.I42.5 cement, 0.05 parts by weight of polyaspartic acid and 0.2 parts by weight of carboxymethyl chitosan, and mix them evenly to obtain a cement-based cementitious material with tuff powder mixed with polymer-controlled material, denoted as R2.
[0043] Comparative Example 3 Weigh 50 parts by weight of tuff powder, 27.5 parts by weight of blast furnace slag powder, 10 parts by weight of desulfurized gypsum powder and 12.5 parts by weight of steel slag powder, and mix them evenly to obtain tuff-based solid waste cementitious material, denoted as R3.
[0044] Comparative Example 4 Weigh out 68 parts by weight of blast furnace slag powder, 12 parts by weight of desulfurized gypsum powder, and 20 parts by weight of steel slag powder, and mix them evenly to obtain a solid waste cementitious material without tuff powder, denoted as R4.
[0045] Comparative Example 5 Weigh out 40 parts by weight of fly ash, 40 parts by weight of blast furnace slag powder, 12 parts by weight of fluorogypsum powder, 8 parts by weight of carbide slag powder, 0.05 parts by weight of polyaspartic acid and 0.2 parts by weight of carboxymethyl chitosan, and mix them evenly to obtain a polymer-controlled fly ash-based solid waste cementitious material, denoted as R5.
[0046] According to GB / T17671-2021 "Test Method for Strength of Cement Mortar", the cementitious materials prepared in Examples 1-6 and Comparative Examples 1-5 were used for mortar molding, and their 3-day, 7-day, and 28-day compressive strength and flexural strength were tested. The results are as follows: Figures 1-2 As shown in Table 2. Figure 1 The graph shows the flexural strength of the cementitious materials after molding in Examples 1-5 and Comparative Examples 1-5. Figure 2 The chart shows the compressive strength of the cementitious materials after molding in Examples 1-5 and Comparative Examples 1-5.
[0047] According to GB / T1346-2024 "Test Methods for Standard Consistency Water Requirement, Setting Time and Soundness of Cement" and GB / T2419-2005 "Test Method for Flowability of Cement Mortar", the setting time of the cement paste and the flowability of the mortar prepared in Examples 1-6 and Comparative Examples 1-5 were tested respectively, and the results are shown in Table 2.
[0048] XRD was used to analyze the hydration products of the paste samples prepared in Example 2 at 3d and 7d ages. The results are as follows: Figure 3 As shown. Figure 3 The XRD pattern of Example 2 (AFt: ettringite; C2S: dicalcium silicate; H: hydrated calcium silicate; Gi: calcium hydrate zeolite; Gy: calcium sulfate dihydrate; Q: quartz).
[0049] like Figure 1As shown, the strength of Comparative Example R1 at all ages is at a low level, indicating that the introduction of high tuff powder content significantly reduces the strength development of cement-based materials. When the tuff powder content reaches 40%, the 28-day compressive strength of the mortar decreases to 24.85 MPa. This is mainly because tuff powder contains a large amount of quartz and a small amount of low-activity minerals such as mica and feldspar. Its large-scale incorporation into the cement system produces a significant dilution effect, reducing the proportion of effective reactive components in the system and thus limiting the hydration reaction process. Similar phenomena exist in solid waste-based cementitious material systems; when the tuff powder content reaches 50%, the mortar strength decreases by 49.11%. However, under the action of polymer reaction regulators, the strength reduction trend of high-tuff powder all-solid waste cementitious materials is significantly improved. When the tuff powder content is 40%~65%, the strength reduction is controlled within 12.95~23.5%. When the dosage of the additive is appropriate, the strength of the resulting cementitious material is even slightly higher than that of the solid waste-based cementitious material without tuff powder, indicating that polymer reaction regulation can promote the participation of low-activity tuff powder in the system reaction and improve the synergistic utilization efficiency of solid waste components.
[0050] As shown in Table 2, due to the surface structure and mineral composition characteristics of tuff powder particles, its large-scale incorporation reduces the flowability of the system and delays the setting process of the cementitious material. In solid waste-based cementitious material systems, high tuff powder content also leads to decreased mortar flowability and prolonged setting time. After introducing a polymeric reaction regulator, the system's flowability is significantly improved, and the setting time tends to shorten. This may be because the polymeric regulator can adsorb onto the surface of tuff particles, improving particle dispersion through steric hindrance, and simultaneously reducing the rapid local deposition of early hydration products through dynamic regulation of reactant ions, thus maintaining a more uniform reaction environment and improving the workability of the cementitious material.
[0051] Table 2 shows the setting time and fluidity of the mortar in Examples 1-6 and Comparative Examples 1-5.
[0052] Table 3. Strength of cementitious mortars prepared in Examples 1-6 and Comparative Examples 1-5 after molding
[0053] Further XRD analysis of the evolution of hydration products in the cementitious material of Example 2 at different ages revealed a significant change in the types of hydration products as the hydration age increased. In the 3-day sample, the ettringite diffraction peak was more prominent, indicating that the early sulfate activation promoted the dissolution of the aluminum phase in the active component and preferentially generated ettringite-like crystalline hydration products. As the hydration reaction continued, the ettringite diffraction peak in the 7-day sample significantly weakened compared to the 3-day sample, while the diffraction peaks related to hydrated calcium silicate gradually strengthened, indicating that the main hydration products in the system gradually shifted from the early-formed crystalline ettringite to the later-formed hydrated calcium silicate and gel products. Simultaneously, the dicalcium silicate diffraction peak significantly decreased from 3 to 7 days, indicating that the mineral phase continued to participate in the reaction during this stage, providing a source of reactants for the later formation of C-(A)-SH gel.
[0054] The above results indicate that polymeric reaction regulators can regulate the reaction process of tuff powder and active solid waste components, promote the formation of gel structures in the later stage, and thus improve the mechanical properties of cementitious materials.
[0055] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A tuff-based all-solid waste cementitious material, characterized in that, The following components are included in the following weight percentages: 40-70 parts tuff powder, 20-50 parts blast furnace slag powder, 5-15 parts sulfate-containing solid waste powder, 5-16 parts alkaline solid waste powder, and 0.01-1.5 parts polymer reaction regulator. The functional groups of the polymer reaction regulating agent include one or more of carboxyl, amino, hydroxyl and sulfonic acid groups; The tuff-based solid waste cementitious material does not include strongly alkaline activators.
2. The tuff-based solid waste cementitious material according to claim 1, characterized in that, The sulfate-containing solid waste powder includes one or more of desulfurized gypsum powder, fluorogypsum powder, and phosphogypsum powder.
3. The tuff-based solid waste cementitious material according to claim 1, characterized in that, The alkaline solid waste powder includes one or more of steel slag powder, red mud powder, and calcium carbide slag powder.
4. The tuff-based solid waste cementitious material according to claim 1, characterized in that, The polymer reaction regulating agent includes one or more of polyaspartic acid, polyethyleneimine, polyallylamine, polyvinyl alcohol, polyvinylpyrrolidone, sulfonated polystyrene, and carboxymethyl chitosan.
5. The tuff-based solid waste cementitious material according to claim 1, characterized in that, The mass of the tuff powder shall not be less than 40% of the total mass of all components of the tuff-based solid waste cementitious material.
6. The tuff-based solid waste cementitious material according to claim 1, characterized in that, The polymer reaction regulating agent is polyvinylpyrrolidone and carboxymethyl chitosan.
7. The tuff-based solid waste cementitious material according to claim 6, characterized in that, The mass ratio of polyvinylpyrrolidone to carboxymethyl chitosan is 1:
4.
8. The tuff-based solid waste cementitious material according to claim 1, characterized in that, The following components are included in the following weight percentages: 50 parts tuff powder, 27.5 parts blast furnace slag powder, 10 parts desulfurized gypsum powder, 12 parts steel slag powder, 0.05 parts polyvinylpyrrolidone, and 0.2 parts carboxymethyl chitosan.
9. A method for preparing the tuff-based solid waste cementitious material according to any one of claims 1 to 8, characterized in that, Includes the following steps: The components of the tuff-based solid waste cementitious material are mixed to obtain the tuff-based solid waste cementitious material.
10. A gelling substance, characterized in that, The preparation materials include the following: water, the tuff-based solid waste cementitious material according to any one of claims 1 to 8, or the tuff-based solid waste cementitious material prepared by the preparation method according to claim 9.